Desafios jurídicos na proteção do sistema agüífero guarani - Guimarães, Luiz Ricardo (2007)
The concern about fresh water reserves on the planet has grown in the last decades of the 20th century and the beginning of the 21st due to the pollution and the increasing consumption generated by society s industrial, agricultural and demographic advancement. However, the fresh water existing in the Earth has been practically the same for thousands of years and it is intrinsically connected to the maintenance of life. There already are regions on Earth that suffer due the absence of such precious environmental resource, and there are forecasts of increase of the global shortage. In this scene, it was divulgated, only with preliminary studies, one of the largest subterranean water reserves of the world, located between Brazil, Argentina, Paraguay and Uruguay: the Guarani Aquifer System. It has been divulged on the media as an immense box of mineral water protected from the evil advancement of modern civilization, and that was available to solve all of the water problems. Such reserve exists, but there are disagreements about its dimension, interconnection and waters´ quality. Anyway, the Guarani arouses the most diverse economic interests in areas such as public supplying, agriculture, thermal, industry, among many others, for being a strategic reserve for a not so distant future. To avoid it s degradation and super exploration, the legislation that protects it and rules it s administration must be efficient, because it s decontamination is practically unviable, besides it s reserves may exhaust. The first obstacle is the lack of conclusive scientific studies, what generates the need of the norms attempt to the precaution principle. The greatest challenge is that Guarani Aquifer System is part under the Estate, federal and international control areas at the same time. There is no legislation specific about Guarani, been it included in the subterranean waters protection. Brazilian s environmental legislation is considered one of the world s most moderns. Including diverse environmental principles and having a specific space for water resources. Besides, with the National Politic of Water Resources being implanted since a decade ago, there are administration systems in advanced development. In Mercosul ambit, the environmental protection system as a whole did not left the theorist field. In the event of conflicts, arbitral courts may be used. Internationally, the environmental defense mechanisms are mostly in the ambit of ONU. Many conferences took place and its ideas were and still are used for the advance of environmental protection. The efficacy of the international system is too restricted and depends on the good will of the involved countries because of sovereignty s questions. The Guarani Aquifer System needs a plain administration, mostly on the national level, because its larger part is located inside Brazilian territory, but it also depends on boundary agreements, under safeguard and advisement of law and international organizations to attempt, in its exploration, the principle of sustainable development and to have, as a primordial finality, the provision for human use, in opposite to economic interests that would benefit only a selected group